Det norske skyldeie - et særnorsk fænomen? - Dørum, Knut (Historisk Tidsskrift, 2013)
Land Rent Ownership In Norway - A Peculiarity of the Norwegians?There seems to be a wide-spread conception among Nordic agrarian historians that the right to land property in the form it existed in Norway from the thirteenth to the eighteenth century, namely land-rent ownership (skyldeie), i.e., ownership of the right to receive rent from landed property rather than ownership of the land as such, was a peculiarly Norwegian phenomenon. An outstanding exponent of this idea was the Norwegian agrarian historian Andreas Holmsen. The author of the present study has nevertheless found a number of examples, especially in Danish sources, that justify a rejection of Holmsen’s construction of the property system as uniquely Norwegian. For in Denmark as well, the annual land rent (skylden) of the Late Middle Ages and Early Modern Period functioned as a measure of land ownership in purchase, sale, and not the least, inheritance. The landowner could likewise possess a partial rent right or shares in the farm’s rent right, an arrangement that merely entailed a right to a portion of the farm’s income, but not the right of physical disposal. Like Norwegian land-rent ownership, the Danish annual land rent was the direct consequence of a predominant property and rent structure in the Late Middle Ages. The ownership of land functioned first and foremost as a source of rents; the landowners at that time rarely conceived of subdividing farms and plots or demanding the use of certain areas of a farm. Moreover, many of the tenant leases were tied into a complicated system of commons, some of them inhibiting the physical division of the farms involved; and in some forms of inheritance the cultivation systems would require a subdivision of rents and shared rent ownership. Furthermore, since the principle of justice was frequently applied in inheritance cases among the nobility, noble families seeking to divide the inheritance of farms with the greatest possible justice to the heirs could resort to a division of the annual land rents. On the other hand, Danish letters from the Late Middle Ages bear witness to the rarity of donating, bequeathing, selling, or panting rent shares to ecclesiastical institutions as well as other kinds of transactions involving rent shares. The Zealand Ecclesiastical Land Record (Sjællands Stifts Landebog) from 1567 shows quite clearly that the kind of donations made by the peasants to the parish churches and the clergy were small single plots, fields, crofts, cattle enclosures, or a house. A cursory examination of the tax record of 1662 shows with great clarity that cases of rent division in Denmark were modest in number compared, for instance, with those recorded in Norway in 1647. For the dominant pattern in Denmark was that one or more entire farms or even villages were owned by one person, while in central parts of Norway it was generally the rule that two or more persons held shares in one and the same farm.In the course of the sixteenth and seventeenth centuries interest in the form of ownership underwent a change in Denmark. The right of disposal of landed property and its potential as a source of income increasingly became a motive in property transactions. Parallel with the growth of demesne production, the acquisition of surrounding properties, and the development of manorial rights (primarily tenant labour), manorial status acquired greater attraction as an object of ownership. Compared to the older rent-owner the manorial owner (herlighetseieren) personified sovereign landownership - in possession of far greater rights than his predecessor. In Norway the right of bygsel, like manorial rights (herlighetsrettigheter) in Denmark, replaced rent ownership as the real object of ownership from around the middle of the seventeenth century. The right of bygsel gave the owner of the largest share of land rent the right to determine the successor of the tenant and to ensure the collection of the rent. In Norway, too, it was new owner interests that brought about the changes in the concept of property. This is seen in the way the right of rent ceded in importance to the right of disposal of the farm, its prerogatives and its appurtenances. We have seen that there were many similarities between the Danish and the Norwegian property systems, although agrarian society in the two countries was obviously very different in many ways. The fact remains that a system of land-rent rights existed in both countries. In Sweden, too, examples can be found of rent ownership, e.g., in the Skara Ecclesiastical Land Record for 1540. It is also likely that similar forms of ownership can be found in other countries such as England, France, and Germany.Translated by Michael Wolfe